Impact analysis of thermally pre-damaged reinforced concrete slabs: Verification of the 3D FE model. (November 2019) - Ožbolt, Joško; Ruta, Daniela; İrhan, Barış
Highlights: 3D FE simulations of thermally pre-damaged reinforced concrete slabs loaded by impact of stiff hammer are performed. Numerical thermo-mechanical and multi-body dynamic analyses are based on the temperature and rate dependent microplane model. Impact simulation is based on the explicit multi body dynamic analysis and contact algorithm with adaptive element deletion technic. It is shown that the simulation is able to realistically replicate the experimental tests and that pre-damage of RC slab through fire reduces impact resistance of the slabs. Abstract: To verify recently developed coupled thermo-mechanical and multi-body dynamic finite element (FE) code the influence of thermally induced damage of reinforced concrete (RC) slabs on their impact properties is numerically investigated. The RC slabs are first pre-damaged through fire load and then loaded by impact of hammer. Transient 3D FE thermo-mechanical analysis is performed. Subsequently, impact simulation is conducted that is based on the explicit multi body dynamic analysis and contact algorithm with adaptive element deletion technic. As a constitutive law for concrete rate and temperature dependent microplane model is employed. The co-rotational Cauchy stress tensor and Green-Lagrange strain tensor are used in the framework of total Lagrange FE formulation. The numerical results are discussed and compared with those obtained experimentally. It is shown that the simulation is able to realistically replicate the experimental tests and that the pre-damage of RC slab through fire significantly reduces impact resistance of RC slabs.